2021
DOI: 10.29040/jap.v21i02.1817
|View full text |Cite
|
Sign up to set email alerts
|

Financing Diversification and Profitability of Islamic Banking in Indonesia

Abstract: This study aims to determine the effect of Islamic bank financing diversification based on economic sectors and based on the type of use on profitability. This study uses financing data for Islamic Banks and Islamic Business Units in 2014-2018. The data in this study are the times series data. Data analyzed by used multiple linear regression analyses. This research provides that results that the HHI of diversification of Islamic bank financing based on the economic sector is positively related to increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Accordingly, the result shows that the concentration of sectoral financing has a negative effect on profitability, supporting the diversification stability hypothesis. This finding is in line with previous findings where the concentration of sectoral financing negatively affects the profitability of Islamic banks (Hamid & Ibrahim, 2020;Šeho et al, 2021;Prastiwi & Anik, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Accordingly, the result shows that the concentration of sectoral financing has a negative effect on profitability, supporting the diversification stability hypothesis. This finding is in line with previous findings where the concentration of sectoral financing negatively affects the profitability of Islamic banks (Hamid & Ibrahim, 2020;Šeho et al, 2021;Prastiwi & Anik, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Both studies documented that financing concentration negatively impacts profitability. Prastiwi and Anik (2021) also found that sectoral financing concentration lowers the profitability of Indonesian Islamic banks. However, previous studies have not distinguished between Islamic commercial banks (ICBs) and Islamic windows banks (IWBs).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…According to the research findings of (Oktavia & Musdholifah, 2018) (Lotfalipour & Bazargan, 2020) (Abdelaziz et al, 2022), (Rizal et al, 2021), one of the macro variables that positively and significantly affects bank profitability is the rate of inflation.. Because people's decisions about what to save and invest depend on their income, inflation has a beneficial impact on profitability. In the meantime, study findings by penelitian (Bahjat et al, 2022) (Gumbo et al, 2022) (Prastiwi, 2022) demonstrate that inflation significantly and negatively affects bank profitability. A high rate of inflation indicates a high rate of price growth overall.…”
Section: Inflationmentioning
confidence: 99%